Evaluation of PCB Shielding Characteristic in Near Field - Yih Jian Chuah; Mohd Tafir Mustaffa (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Wireless electronic devices nowadays always operate in high frequency while having small and compact form factor which led to electromagnetic interference among traces and components. PCB shielding is the common solution applied in electronic industry to mitigate electromagnetic interference. In this paper, PCB shielding characteristics such as shield’s thickness, height, and ground via spacing in PCB boards were evaluated in near field. Test boards with various ground via spacing were fabricated and evaluated by using 3D Electromagnetic scanner. On the other hand, shields with various thickness and height were modeled and evaluated through simulation. Results suggested that shielding effectiveness could be improved by having greater shield’s height with smaller ground via spacing in shielding ground tracks. Shielding effectiveness can be improved by 1 dB with every step of 0.5 mm increase in shield’s height. Besides that, approximately 0.5 dB improvement in shielding effectiveness with every step of 1 mm decrease in ground via spacing. Furthermore, greater shield’s thickness can contribute better shielding effectiveness for operating frequency below 300 MHz.